UPAYA HUKUM PENYELESAIAN SENGKETA KONSUMEN APARTEMEN TERKAIT KETIDAKSESUAIAN LUAS SEMIGROSS UNIT DALAM PERJANJIAN PENGIKATAN JUAL BELI - Adrian Winata; Sri Bakti Yunari (Fakultas Hukum Universitas Tarumanagara, 2020)
The development and marketing of the flat itself can be done by the state or by the developer, construction and marketing of the flat carried out by PT. Binakarya Citra Buana had harmed Mr. Erison and the consumer ended up with a lawsuit. Is the decision of the West Java High Court Number. 190 / PDT / 2018 / PT.BDG is against the Consumer Protection Law Number. 8 of 1999 concerning the extent of agreed non-compliance and what efforts can these consumers do to take back the rights of those who have been harmed by the developer? The research method used is normative juridical research using secondary legal materials that are analyzed conclusively with a legal and case approach. Based on the results of the analysis it is proven that the court's decision is not in accordance with the Consumer Protection Law Number. 8 of 1999 and legal remedies submitted by consumers are not in accordance with the Consumer Protection Act. Legal remedies to be done by Mr. Erison must consult with a legitimate consumer protection body before filing a lawsuit in court. Based on the results of dining research it has been proven that Pt. Binakarya Citra Buana has violated several provisions contained in the Consumer Protection Act, As a suggestion there needs to be a socialization about the rights and obligations of consumers as well as a socialization about the existence of Institutions and Consumer Protection Institutions.